Subcellular localization of Na/K-ATPase isoforms in ventricular myocytes. (July 2017) - Yuen, Garrick K.; Galice, Samuel; Bers, Donald M.
Abstract: The sodium/potassium ATPase (NKA) is essential for establishing the normal intracellular [Na + ] and [K + ] and transmembrane gradients that are essential for many cellular functions, including cardiac electrophysiology and contractility. Different NKA isoforms exhibit differential expression levels, cellular localization, and function in different tissues and species. Prior work has indicated that the NKA-α1 isoform is quantitatively predominant in cardiac myocytes, but that the α2 isoform is preferentially concentrated in the transverse tubules (TT), possibly at junctions with the sarcoplasmic reticulum (SR) where α2 may preferentially modulate cardiac contractility. Here we measured subcellular localization of NKA-α1 and α2 using super-resolution microscopy (STED and STORM) and isoform-selective antibodies in mouse ventricular myocytes. We confirm the preferential localization of NKA-α2 in TT vs. surface sarcolemma, but also show that α2 is relatively excluded from longitudinal TT elements. In contrast NKA-α1 is relatively uniformly expressed in all three sarcolemmal regions. We also tested the hypothesis that NKA-α2 (vs. α1) is preferentially concentrated at SR junctional sites near ryanodine receptors (RyR2). The results refute this hypothesis, in that NKA-α1 and α2 were equally close to RyR2 at the TT, with no preferential NKA isoform localization near RyR2. We conclude that in contrast to relatively uniform NKA-α1 distribution, NKA-α2 is preferentially concentrated in the truly transverse (and not longitudinal) TT elements. However, NKA-α2 does not preferentially cluster at RyR2 junctions, so the TT NKA-α2 concentration may suffice for preferential effects of NKA-α2 inhibition on cardiac contractility. Highlights: STED and STORM imaging confirms prior work showing higher NKA-α2 density in T-tubules (TT) vs. surface sarcolemma (SSL). STED and STORM confirms higher uniformity for NKA-α1 than NKA-α2 throughout the cardiac myocyte. NKA-α2 is localized to transverse TT elements, while α1 is in both transverse and longitudinal TT elements. NKA-α2 may be more concentrated just below the TT openings near the SSL. Ryanodine receptor clusters are not closer to NKA-α2 vs. α1 (dispelling a prior hypothesis).